Fasciola hepatica Immune Regulates CD11c+ Cells by Interacting with the Macrophage Gal/GalNAc Lectin - Rodríguez, Ernesto; Carasi, Paula; Frigerio, Sofía; da Costa, Valeria; van Vliet, Sandra; Noya, Verónica; Brossard, Natalie; van Kooyk, Yvette; García-Vallejo, Juan J.; Freire, Teresa (Frontiers in Immunology, 2017)
Fasciolosis, caused by Fasciola hepatica and Fasciola gigantica, is a trematode zoonosis of interest in public health and livestock production. Like other helminths, F. hepatica modulates the host immune response by inducing potent polarized Th2 and regulatory T cell immune responses and by downregulating the production of Th1 cytokines. In this work, we show that F. hepatica glycans increase Th2 immune responses by immunomodulating TLR-induced maturation and function of dendritic cells (DCs). This process was mediated by the macrophage Gal/GalNAc lectin (MGL) expressed on DCs, which recognizes the Tn antigen (GalNAc-Ser/Thr) on parasite components. More interestingly, we identified MGL-expressing CD11c+ cells in infected animals and showed that these cells are recruited both to the peritoneum and the liver upon F. hepatica infection. These cells express the regulatory cytokines IL-10, TNFα and TGFβ and a variety of regulatory markers. Furthermore, MGL+ CD11c+ cells expand parasite-specific Th2/regulatory cells and suppress Th1 polarization. The results presented here suggest a potential role of MGL in the immunomodulation of DCs induced by F. hepatica and contribute to a better understanding of the molecular and immunoregulatory mechanisms induced by this parasite.